Pengaruh Bencana Covid-19 Dan Pembatasan Sosial Terhadap Perubahan Perilaku Konsumen (Studi Kasus Pada Konsemen Industri Kerupuk Rambak Di Mojokerto) - Ilmi Rahmawati; Agus Widarko; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis research was conducted with the aim of analyzing the variables of the Covid-19 Disaster and Social Distancing on Changes in Consumer Behavior in consumers of the rambak cracker industry in Mojokerto simultaneously and partially. This research uses explanatory research with descriptive and quantitative approaches. The population in this study were consumers of the Cow Jaya rambak cracker industry located in Hamlet Kauman, Bangsal Village Rt 06/15 Bangsal District, Mojokerto Regency, East Java. The sampling technique used was Non Probability Sampling which was assisted by the Slovin formula, so a sample of  52 respondents was obtained. Data analysis using multiple linear regression analysis processed with SPSS 16.0 software. The survey method used was a questionnaire. The results showed that the Covid-19 Disaster and Social Restrictions simultaneously had a significant effect on changes in consumer behavior. And the Covid-19 Disaster variable partially has no significant effect on changes in consumer behavior. Social Restrictions Variable has a partially significant effect on Changes in Consumer Behavior. Keywords: Covid-19 Disaster, Social Distancing, Changes in Consumer Behavior